Errata: Communications - Scientific Letters of the Zilina, vol. 19, No. 2, 2017, ``Incorporating Bicycles into Urban Mobility: An Opportunity for Sustainable Development'', pp. 68-73. - Lopez-Escolano, Carlos; Campos, Angel Pueyo; Pardos, Sergio Valdivielso; Nedeliakova, Eva; Stefancova, Vladimira (Communications - Scientific Letters of the University of Zilina, 2017)
Errata: Communications - Scientific Letters of the Zilina, vol. 19, No. 2, 2017, ``Incorporating Bicycles into Urban Mobility: An Opportunity for Sustainable Development'', pp. 68-73. The proper quotations [12] and [19] should be referred to as follows:[12] PUEYO CAMPOS, A., LOPEZ-ESCOLANO, C., DIESTE HERNANDEZ, J.: Moving Towards Sustainable Mobility in Zaragoza (Spain): The Bicycle as a Mode of Urban Transport. Consensus, Paralysis and Conflicts in an Effervescent Model [L'Evolution de Saragosse vers la mobilite durable: Le elo comme mode de transport urbain. Consensus, paralysie et conflits d'un modele en effervescence]. Sud-Ouest Europeen, 40, 2015, pp. 101-114, ISSN 12764930.[19] ARRANZ-LOPEZ, A., SORIA-LARA, J., LOPEZ-ESCOLANO, C., PUEYO CAMPOS, A.: Retail Mobility Environments: A Methodological Framework for Integrating Retail Activity and Non-motorised Accessibility in Zaragoza (Spain). J. of Transport Geography, 58, 2017, pp. 92-103, ISSN 09666923.
Keywords: Errata: Communications - Scientific Letters of the Zilina; vol. 19; No. 2; 2017; ``Incorporating Bicycles into Urban Mobility: An Opportunity for Sustainable Development''; pp. 68-73.